2021
DOI: 10.3390/insects12121057
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cold Storage on Host Antheraea pernyi Egg Quality for the Egg Parasitoid Anastatus fulloi Sheng and Wang

Abstract: Chinese silkworm (Antheraea pernyi) eggs are used as factitious hosts of Anastatus fulloi, and refrigeration of these eggs is essential for large-scale rearing of A. fulloi. We studied the effects of cold storage of A. pernyi eggs on egg quality and the fitness of A. fulloi reared on the eggs. Four cold storage treatments and two cold storage periods were assessed. The 0–3 °C refrigerator treatment was unsuitable for long-term (>70 days) storage. Cold storage at −5 °C and −18 °C increased the loss rate of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Infertile eggs are collected from emerged female moths in the following year and can be stored at −10 °C for up to 6 months for mass rearing of Anastatus species 18 . Recent study showed that no significant differences in emergence rate and the proportion of Anastatus fulloi females when reared on Antheraea pernyi eggs stored at −5 °C and −18 °C for 6 months compared to fresh eggs, whereas the parasitism rate was reduced after 6 months cold storage and still reach over 90% on average 36 . Nonetheless, cold storage of Antheraea pernyi eggs should not exceed 6 months to have limited negative effects to maintain higher level productivity in mass rearing of Anastatus species 18,36 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Infertile eggs are collected from emerged female moths in the following year and can be stored at −10 °C for up to 6 months for mass rearing of Anastatus species 18 . Recent study showed that no significant differences in emergence rate and the proportion of Anastatus fulloi females when reared on Antheraea pernyi eggs stored at −5 °C and −18 °C for 6 months compared to fresh eggs, whereas the parasitism rate was reduced after 6 months cold storage and still reach over 90% on average 36 . Nonetheless, cold storage of Antheraea pernyi eggs should not exceed 6 months to have limited negative effects to maintain higher level productivity in mass rearing of Anastatus species 18,36 .…”
Section: Discussionmentioning
confidence: 99%
“… 18 Recent study showed that no significant differences in emergence rate and the proportion of Anastatus fulloi females when reared on Antheraea pernyi eggs stored at −5 °C and −18 °C for 6 months compared to fresh eggs, whereas the parasitism rate was reduced after 6 months cold storage and still reach over 90% on average. 36 Nonetheless, cold storage of Antheraea pernyi eggs should not exceed 6 months to have limited negative effects to maintain higher level productivity in mass rearing of Anastatus species. 18 , 36 Moreover, manually extracted, infertile and washed Antheraea pernyi eggs are most suitable for mass rearing of Anastatus species, including Anastatus japonicus .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this study did not examine the number of L. delicatula nymphs that emerged from freshly collected L. delicatula egg masses, those stored at 5°C, or what nymph emergence rates would be if eggs were stored at temperatures below 5°C (e.g., -40°C) for varying time periods. Previous studies have shown that parasitoid species in the genus Anastatus were able to parasitize frozen hemipteran and lepidopteran eggs ( 19 , 20 ). However, it is unknown if fulgorid egg masses (e.g., L. delicatula ) would be suitable for parasitism by A. orientalis after freezing.…”
Section: Introductionmentioning
confidence: 99%